Dogs display owner-specific expectations based on olfaction - Juliane Bräuer (Nature Portfolio, 2021)
Abstract Most current knowledge about dogs’ understanding of, and reacting to, their environment is limited to the visual or auditory modality, but it remains unclear how olfaction and cognition are linked together. Here we investigate how domestic dogs search for their owners using their excellent olfactory sense. We raise the question whether dogs have a representation of someone when they smell their track. The question is what they expect when they follow a trail or whether they perceive an odour as a relevant or non-relevant stimulus. We adopted a classical violation-of-expectation paradigm—and as targets we used two persons that were both important to the dog, usually the owners. In the critical condition subjects could track the odour trail of one target, but at the end of the trail they find another target. Dogs showed an increased activity when the person did not correspond with the trail compared to a control condition. Moreover, we found huge individual differences in searching behaviour supporting the assumption that dogs are only able to smell when they really sniff, and that the temperature has an influence on dogs performance. Results are discussed in the light of how cognitive abilities, motivation and odour perception influence each other.